2017
DOI: 10.3390/f8040127
|View full text |Cite
|
Sign up to set email alerts
|

Sydowia polyspora Dominates Fungal Communities Carried by Two Tomicus Species in Pine Plantations Threatened by Fusarium circinatum

Abstract: Bark beetles (Coleoptera, Scolytinae) carry a diverse filamentous fungal community sometimes acting as vectors or carriers of phytopathogens. In this study, mycobiota carried by two Tomicus species (Tomicus piniperda and Tomicus destruens) were investigated through (i) morphological and molecular identification of taxa; (ii) taxonomic richness, diversity, evenness, dominance and phoresy indices; (iii) ecological network analysis and (iv) statistical co-occurrence analysis. The studied mycobiota were formed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 77 publications
(96 reference statements)
1
22
0
Order By: Relevance
“…Different bark beetles were shown to be vectors for S. polyspora, which can rapidly spread and colonise trees following beetle attacks [51,52]. In addition, S. polyspora might also benefit from the forest damage caused by other pathogens [53]. As in the present study, the collected needles were healthy-looking, the establishment of S. polyspora was probably latent.…”
Section: Discussionsupporting
confidence: 57%
“…Different bark beetles were shown to be vectors for S. polyspora, which can rapidly spread and colonise trees following beetle attacks [51,52]. In addition, S. polyspora might also benefit from the forest damage caused by other pathogens [53]. As in the present study, the collected needles were healthy-looking, the establishment of S. polyspora was probably latent.…”
Section: Discussionsupporting
confidence: 57%
“…This insect species has been proposed as a plausible vector of the disease in the study region, where 12% of the shoots collected from the ground were found to be associated with the pathogen in plantations affected by PPC [22]. However, the pathogen was not found in association with specimens of T. piniperda and T. destruens analyzed by Muñoz-Adalia et al [60] in the same study area, although other Fusarium spp. were detected.…”
Section: Discussionmentioning
confidence: 65%
“…Sydowia polyspora was also found to be the dominant fungal species carried by insects ( Tomicus spp.) feeding on pine shoots, although the fungus–insect–plant interaction remains unclear (Muñoz‐Adalia et al, ).…”
Section: Resultsmentioning
confidence: 99%